2012
DOI: 10.1093/eurheartj/ehs290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac surgery with left atrial surgical ablation vs. cardiac surgery without atrial ablation in patients with coronary and/or valvular heart disease plus atrial fibrillation: final results of the PRAGUE-12 randomized multicentre study

Abstract: AimsSurgical ablation procedure can restore sinus rhythm (SR) in patients with atrial fibrillation (AF) undergoing cardiac surgery. However, it is not known whether it has any impact on long-term clinical outcomes.Methods and resultsThis multicentre study randomized 224 patients with AF scheduled for valve and/or coronary surgery: group A (left atrial surgical ablation, n = 117) vs. group B (no ablation, n = 107). The primary efficacy outcome was the SR presence (without any AF episode) during a 24 h electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 31 publications
4
65
0
20
Order By: Relevance
“…Wiele badań obserwacyjnych wskazuje na praktyczne możliwości i bezpieczeństwo chirurgicznego zamykania/wyłączania LAA, ale dostępne są jedynie ograniczone dane z kontrolowanych prób klinicznych [461][462][463][464]. Rezydualny przepływ w LAA lub niepełne wyłączenie LAA może zwiększać ryzyko udaru mózgu [465].…”
Section: Chirurgiczne Zamykanie Lub Wyłączanie Uszka Lewego Przedsionkaunclassified
See 1 more Smart Citation
“…Wiele badań obserwacyjnych wskazuje na praktyczne możliwości i bezpieczeństwo chirurgicznego zamykania/wyłączania LAA, ale dostępne są jedynie ograniczone dane z kontrolowanych prób klinicznych [461][462][463][464]. Rezydualny przepływ w LAA lub niepełne wyłączenie LAA może zwiększać ryzyko udaru mózgu [465].…”
Section: Chirurgiczne Zamykanie Lub Wyłączanie Uszka Lewego Przedsionkaunclassified
“…W następstwie zabiegu labiryntowania według Coxa wytworzony więc zostaje elektryczny labirynt (maze), w którym pobudzenie z węzła zatokowo-przedsionkowego znajduje drogę do węzła przedsionkowo-komorowego, a jednocześnie zapobiega się przewodzeniu migoczącemu. Zabieg labiryntowania według Coxa oraz inne, często prostsze, metody chirurgicznego leczenia AF wykonuje się głównie u pacjentów poddawanych innej operacji na otwartym sercu [461,466,[784][785][786][787][788][789][790][791][792][793][794][795][796][797][798]. W przeglądzie systematycznym zamówionym na potrzeby niniejszych wytycznych stwierdzono, że chirurgiczne leczenie AF przy okazji innej operacji kardiochirurgicznej zwiększało odsetek pacjentów bez AF, trzepotania przedsionków lub częstoskurczu przedsionkowego w porównaniu z niestosowaniem takiego leczenia (RR 1,94; 95% CI 1,51-2,49; n = 554 w 7 RCT) (dodatkowa ryc.…”
Section: Obserwacja Po Ablacji Przezcewnikowejunclassified
“…1290 Several other RCTs and meta-analyses are available to evaluate AF surgery at the time of concomitant mitral procedures. 1327,1328,1329,1330,1331,1332,1333,1334 Large LA, AF duration, advanced age, and failure to isolate the entire posterior LA are common predictors of reduced long-term efficacy. High baseline comorbid risk is a common reason cited for not performing surgical ablation, though many institutional studies note that this is not a contraindication to surgical ablation.…”
Section: Section 12: Surgical and Hybrid Af Ablationmentioning
confidence: 99%
“…LAAOS III-a large, randomized prospective trial designed to compare the efficacy of LAA closure for stroke prevention using excision versus stapled closure, to no closure at all (21)-may ultimately address this issue. For now, the findings from the PRAGUE-12 study (22) seem to provide preliminary support in favor of complete LAA closure. This study found that the incidence of stroke among those who underwent LAA surgical excision in conjunction with AF surgery was 2.7% at 1 year, as compared to 4.3% in the control arm.…”
Section: Other Implicationsmentioning
confidence: 80%